A review paper on aluminium-alumina arrangement of composite materials in automotive brakes. (2020) - Venugopal, S.; Karikalan, L.
Abstract: The two level composite of co perpetual aluminium-alumina arrangement is to circumvent SiC particle which provides thermal conductivity. The Wear of CuSiCpMMC material is analysed by utilizing scam electron as well as optical microscopy of wear cicatrices. The tribological inadequacies of the single phase material and categorical function of sundry type of additives were outlined. The results of test withal show is that a friction material with the steel fiber is not well-matched with the Al-MMC disk because of astringent materials as well as erratic friction comportment through descending at elevated temperature.